Collapse of 3D orthogonal woven carbon fibre composites under in-plane tension/compression and out-of-plane bending composite structures - Turner, Paul; Liu, Tao; Zeng, Xuesen (Elsevier, 2016)
An experimental and numerical investigation was undertaken to characterise the collapse of 3D orthogonal woven carbon fibre composites during the load cases of in-plane tension, inplane compression and out-of-plane bending. Two different fibre architectures, varying only by the density of through-thickness reinforcement, were investigated. Cantilever beam tests were carried out to isolate two distinct collapse mechanisms, i.e. bending governed and shear governed deformation. A qualitative comparison was made with a similar UD-laminate material. 3D woven composites exhibited significantly reduced delamination. An investigation into the efficacy of an embedded element modelling strategy for in-plane tension, in-plane compression and out-of-plane bending load cases was undertaken. The predictions were generally in good agreement with the experimental measurements for the inplane and out-of-plane loading.